Cost-benefit model in improving traceability system: case study in Indonesian bulk-liquid industry. Issue 2 (3rd April 2019) - Gunawan, Ivan; Vanany, Iwan; Widodo, Erwin
ABSTRACT: Traceability system (TS) is a part of a food safety management system to support efficient food recall process. Building a TS for bulk-liquid food industry has been identified as the most difficult task due to its operational characteristics. This paper captures the real phenomenon of TS and food recall in three edible oil industries in Indonesia. Cross-case comparison shows that the TS practices in similar industries may vary. Although, their TS proves to have an effect on their capability to recall, building an excellent TS is costly. Therefore, a cost-benefit model based on a system dynamic approach is proposed to assist the industry in setting the traceability improvement program. The cost-benefit model considers the influence of traceability dimensions on profit and recall cost. The cost-benefit conceptual model is presented in a causal loop diagram. Then, the stock flow diagram runs the simulation improvement scenarios in real case. Scenario 3 is chosen as the best short-term TS improvement program.